2019
DOI: 10.1071/ah17130
|View full text |Cite
|
Sign up to set email alerts
|

Privately practising nurse practitioners' provision of care subsidised through the Medicare Benefits Schedule and the Pharmaceutical Benefits Scheme in Australia: results from a national survey

Abstract: Since legislative changes in 2010, certain health care services provided by privately practising nurse practitioners (PPNPs) in Australia have been eligible for reimbursement under the Medicare Benefits Schedule (MBS) and the Pharmaceutical Benefits Scheme (PBS). The aim of the present study was to describe survey results relating to the care provided by PPNPs subsidised through the MBS and PBS. PPNPs in Australia were invited to complete an electronic survey exploring their practice activities. Quantitative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…To date some 1,839 NPs practice in Australia, however, despite being eligible providers with access to the Medical Benefits Schedule (MBS), NPs in the private sector of the Australian healthcare system are only able to access four consultation, six telehealth, and no procedural MBS item numbers. 29,30 This significantly curtails NP private practice. 22,30 As many patients have multi-morbidities, medical care is increasingly complex, and even routine surgical procedures can involve significant risks.…”
Section: What This Paper Addsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date some 1,839 NPs practice in Australia, however, despite being eligible providers with access to the Medical Benefits Schedule (MBS), NPs in the private sector of the Australian healthcare system are only able to access four consultation, six telehealth, and no procedural MBS item numbers. 29,30 This significantly curtails NP private practice. 22,30 As many patients have multi-morbidities, medical care is increasingly complex, and even routine surgical procedures can involve significant risks.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…29,30 This significantly curtails NP private practice. 22,30 As many patients have multi-morbidities, medical care is increasingly complex, and even routine surgical procedures can involve significant risks. The optimal surgical team should be assembled for all surgical procedures.…”
Section: What This Paper Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research (and experience of the authors) has shown that some MPs do not understand the nature of the collaborative arrangement, reinterpreting it as a supervisory or control relationship. 28 Such an interpretation contradicts the intent of the introduction of NPs initially, 29 and latterly PPNPs, 11 which was to increase access to health services for underserved and marginalised populations through the introduction of a highly skilled nursing workforce that was able to practise autonomously. 30 The persistence of these misunderstandings among some MPs has led to associated concerns about their liability for the actions of NPs and PPNPs.…”
Section: Introductionmentioning
confidence: 99%
“…This includes ordering investigations, interpreting the results and follow up taking appropriate actions to optimise the care. Tempering the historical and contemporary ability of the NP to deliver innovative care in Australia has been and is, the structure of the healthcare system, limited access to the Medical Benefits Schedule (MBS) and the protectionism of others practising in the space (Currie et al, 2019a;Currie et al, 2019b;D'Antonio & Lewenson (2011); Gardner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%